EVALUASI KEBIJAKAN PENGENDALIAN PENGGUNAAN PLASTIK DI KOTA SEMARANG (Studi Kasus Pelaku Usaha di Kecamatan Tembalang) - Perwitasari, Intan; Purnaweni, Hartuti; Rina Herawati, Augustin (Journal of Public Policy and Management Review, 2024)
The policy to control the use of plastic in the City of Semarang is motivated by the high amount of waste, particularly plastic waste, in the City of Semarang. To address this issue, the City Government of Semarang issued Perwali No. 27 of 2019 concerning the control of plastic use in the City of Semarang. This study focuses on business actors, specifically owners of restaurants/cafes/restaurants who still use plastic. The aim of this study is to evaluate the implementation of the plastic use control policy and the inhibiting factors of the Perwali No. 27 of 2019 policy on plastic control. The theories used are the policy evaluation theory by Dunn and the policy implementation success theory by Grindle. This study employs a descriptive qualitative method with the subjects being policy implementers directly involved in Perwali No. 27 of 2019 on plastic use control, selected through purposive sampling. Data collection was conducted through interviews, observations, and documents, while the data analysis used includes data collection, reduction, presentation, and conclusion drawing. The results of the study indicate that many restaurant/cafe/restaurant business actors do not comply with the Perwali; many business actors still use plastic and no sanctions are given. The inhibiting factors for the policy implementation are resource factors and the implementation environment. Thus, awareness and participation from the community, as well as firm action from the City Government of Semarang, are needed.